2015
DOI: 10.5194/ms-6-127-2015
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the particulate flow in cold spray nozzles

Abstract: Abstract. Cold Spray is a novel technology for the application of coatings onto a variety of substrate materials. In this method, melting temperatures are not crossed and the bonding is realized by the acceleration of powder particles through a carrier gas in a converging-diverging nozzle and their high energy impact over a substrate material. The critical aspect of this technology is the acceleration process and the multiphase nature of it. Three different nozzle designs were experimented under constant condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Accordingly, a study by Lupoi [23] showed that a number of experimental observations with various nozzle geometries could not be explained by 1-way coupling CFD techniques. An improvement of the computations was shown to be achievable when increasing the detail of phase coupling for such experiments by Meyer & Lupoi [24]. As for higher particle feed rates, a work by Pattison et al [25] showed an experimental optimisation involving a full 2D-velocity field deduction using PIV in its usual sense.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a study by Lupoi [23] showed that a number of experimental observations with various nozzle geometries could not be explained by 1-way coupling CFD techniques. An improvement of the computations was shown to be achievable when increasing the detail of phase coupling for such experiments by Meyer & Lupoi [24]. As for higher particle feed rates, a work by Pattison et al [25] showed an experimental optimisation involving a full 2D-velocity field deduction using PIV in its usual sense.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical energy released via combustion and electric energy released by formation of arc are the two main sources of energy that elevate the thermal energy of the particles. An innovative advancement in the coating process called the cold spray technique does not involve providing thermal energy, the whole process of coating is executed under the influence of kinetic energy [18][19][20][21][22][23].…”
Section: Thermal Spraying Techniquesmentioning
confidence: 99%
“…The interaction between solid particles and propellant gas in the 3D model was defined using the Lagrangian particle tracking method. Earlier studies have implemented this method to simulate particle transport in the cold spray process [17][18][19]. The 3 D model simulated t h e velocity and temperature for (2 kg/hr) spherical titanium particles as per a typical particle size distribution (5, 12, 26 and 41 µm) for cold spray deposition [6,20,21].…”
Section: Titanium Particlesmentioning
confidence: 99%